THE TIMAN-PECHORA PALEOGEOGRAPHY AND FADES IN THE KUNGURIAN-UFIMIAN BOUNDARY PERIOD - Malysheva E.O.; Kanev G.P.; Koloda N.A. (My University, 2001)
The complicatedly intercalated marine and continental Permian beds of the Timan-Pechora region are subdivided using the combination of the litho- and biostratigraphic methods and the sequence stratigraphy technique. Among the distinguished intervals favorable for paleogeographic reconstructions, one across the Kungurian-Ufimian boundary is considered in this work. The well-studied sections that are exposed in the Uralian foredeep and those recovered by boreholes in the Pechora syneclise are chosen to be the reference ones. The regional correlation is based on the established facies changes along the boundaries of and inside the units of the reference sections. Ten facies-paleogeographic zones are recognized in the Timan-Pechora region for the Kungurian-Ufimian boundary period.
Keywords: Timan-Pechora region; Permian; Paleozoic::Permian; Палеозой::Пермская